Pengalaman Pembelajaran melalui Project-Based Learning untuk Memperkuat Profesionalisme Calon Guru - Angelica Putri Larasati; Ana Maghfiroh; Dwiana Binti Yulianti (Universitas Muhammadiyah Ponorogo, 2026)
Teacher professionalism is widely recognized as a multidimensional construct encompassing pedagogical competence, ethical responsibility, reflective capacity, collaborative engagement, and professional identity formation. However, teacher education programs frequently emphasize theoretical instruction over authentic professional practice, resulting in a gap between conceptual understanding and practical readiness. This study explores how learning experiences structured through Project-Based Learning (PjBL) contribute to strengthening the professionalism of pre-service teachers. This research employed a qualitative case study design grounded in an interpretivist paradigm. Participants were 36 pre-service teachers from the English Education Department of Universitas Muhammadiyah Ponorogo, with complementary perspectives from students at UIN Kiai Ageng Muhammad Besari Ponorogo. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using the interactive qualitative model of Miles, Huberman, and Saldaña. Findings reveal that PjBL fosters professionalism across five interconnected dimensions: cognitive (instructional design and assessment literacy), practical (teaching performance and classroom management), social (collaborative competence and professional communication), reflective (critical self-evaluation), and identity (professional commitment and self-perception as a teacher). The most transformative stages were project planning, teaching simulation, presentation, and structured reflection. Challenges such as time management and performance anxiety functioned as developmental tensions that stimulated resilience and adaptive growth. The study concludes that PjBL operates not merely as an instructional strategy but as a professional formation ecosystem that bridges theory and practice. Its integration within teacher education programs provides a holistic pathway for cultivating adaptive, reflective, and confident future educators.